(±)-Involucrasins A and B, two pairs of flavanone enantiomers from Shuteria involucrata and their inhibitory effects on the proliferation of various cancer cell lines. Issue 7 (3rd July 2022) - Liu, Lu; Li, Xiao-Hong; Ma, Xiao-Xia; Tan, Wen-Hong; Ma, Wen-Zhe; Shen, Yun-Fu; Khan, Afsar; Zhou, Zhi-Hong; Yang, Zhu-Ya
Abstract: (±)-Involucrasins A (1 ) and B (2 ), two pairs of flavanone enantiomers were isolated from Shuteria involucrata . Structurally, both 1 and 2 are rare representatives of 5-dehydroxy/5-demethoxy 2', 3', 4'-trisubstituted flavanones. Their structures were elucidated on the basis of comprehensive spectroscopic data analysis and comparison with the literature data. Involucrasin B (2 ) exhibited moderate anti-proliferative activity against Caco-2, MCF-7, MDA-MB-468, and HCT116 cell lines with IC50 values ranging from 7.9–22.7 μM. Involucrasin A (1 ) exhibited weak inhibitory activity against Caco-2 and MCF-7 cell lines with IC50 values of 25.8 and 26.5 μM, respectively. Abstract : UF0001